Prevalence of Perineural Invasion in keratinocyte cancer in the general population and among organ transplant recipients. (3rd February 2020) - Adams, Agnieszka; Pandeya, Nirmala; De'Ambrosis, Brian; Plasmeijer, Elsemieke; Panizza, Ben; Green, Adele C; Olsen, Catherine M.; Whiteman, David C.
Abstract: Background/Objectives: Basal cell carcinomas (BCCs) and cutaneous squamous cell carcinomas (SCCs) are the most commonly encountered cancers in fair‐skinned populations worldwide. Perineural invasion is associated with worse outcomes for patients with BCC or SCC. Estimates of perineural invasion prevalence range widely, likely reflecting non‐representative patient samples. We sought to determine the prevalence of perineural invasion in BCC and SCC in the general population, as well as among cancers arising in solid organ transplant recipients. Methods: We retrospectively analysed histopathology reports of BCC and SCC from patients enrolled in the QSkin Study (a population‐based cohort of 43 794 Queensland residents recruited 2010–2011) and the Skin Tumours in Allograft Recipients (STAR) study (a cohort of 509 high‐risk kidney or liver transplant recipients at the Princess Alexandra Hospital, Brisbane, recruited 2012–2014.) We estimated the prevalence of perineural invasion (and 95% confidence interval) in BCC and SCC, respectively, and identified clinical factors associated with perineural invasion. Results: In QSkin, we observed 35 instances of perineural invasion in 9850 histopathologically confirmed BCCs (0.36%) and 9 instances of perineural invasion in 3982 confirmed SCC (0.23%) lesions. In the STAR cohort, we identified 4 lesions with perineural invasion in 692 BCCs (0.58%) and 16 reports of perineural invasion in 875 SCC lesions (1.9%). Conclusions: These data suggest that the overall prevalence of perineural invasion in keratinocyte cancer is low, although perineural invasion prevalence may be slightly higher among organ transplant recipients when compared to the general population.